Pediatric Biopharmaceutical Classification Systems (pBCS) - Justyna Srebro; Witold Brniak; Renata Jachowicz; Klaudia Syty; Katarzyna Tomaś (Polish Pharmaceutical Society, 2023)
The biopharmaceutical classification system, proposed in 1995 by Amidon in order to facilitate dissolution studies and to correlate their results with the bioavailability of a drug substance in vivo has been successfully used for almost 30 years in pharmaceutical sciences. It is also reflected in many guidelines on pre-registration testing of drugs, both developed by the European Medicines Agency (EMA), the US Food and Drug Administration (FDA), and the International Council for Harmonization of Technical Requirements for Registration of Medicinal Products for Human Use (ICH). The system includes classifying medicinal substances into 4 classes with different solubility and permeability through biological membranes, which directly impacts the drug's disposition after oral administration. However, its assumptions are based on the model of drug administration to an adult patient, which makes its use in the case of pediatric preparations very difficult. Pediatric patients form a non-uniform group. Along with age, not only the size of the body and its mass are changed. These changes include the development of organs and physiological systems, which is significant in the context of the selection of the dosage form appropriate for the particular development stage. The pediatric population includes a couple of groups: preterm neonates, neonates, infants, toddlers, preschoolers, school-aged children, and teenagers. Their structure is also heterogeneous. This causes the need to individualize therapy and carefully select the drug depending on the patient's age. The need to develop a biopharmaceutical classification system appropriate for pediatric drugs was recognized over 10 years ago. However, there is no uniform system recommended by the EMA, FDA, or ICH so far. The various proposals primarily take into account the proportional reduction of the volume of the medium used to determine the solubility to more closely reflect the volume of gastric juice in children or more often the volume of liquid that a child can take to wash down a drug. To determine the permeability of a drug substance through biological membranes, models similar to those for an adult are used, or the value of the n-octanol/water partition coefficient (logP) is used. There are also more advanced models used, which base on the analysis of pharmacokinetic parameters achieved for oral and parenteral administration.